Antimicrobial Resistance A Global Threat - Kumar, Yashwant (IntechOpen, 2019)
The discovery of antibiotics was considered a milestone in health sciences and became the mainstay of antimicrobial therapy to treat and control bacterial infections. However, its utility has subsequently become limited, due to the emergence and spread of antimicrobial resistance among different bacterial species, which has emerged as a global threat. The development and spread of antimicrobial resistance have been attributed to many factors, including indiscriminate use of antibiotics in the healthcare and livestock industries. The present scenario of antibiotic resistance urgently requires interventions in terms of development of newer antimicrobials, evaluation of alternative therapies, and formulation of stringent policies to curb indiscriminate use of antimicrobials. This book highlights the importance and development of antimicrobial resistance in zoonotic, environmental and food bacteria, including the significance of candidate alternative therapies.